Halogen bonded supramolecular porous structures with a kgm layer. Issue 48 (22nd November 2016) - Cheng, Fujun; Wang, Haijun; Hua, Yinying; Cao, Haifei; Zhou, Bihang; Duan, Jingui; Jin, Wanqin
Abstract : Halogen (Br and I) dependent interactions and effects in water and base stable supramolecular porous structures. Abstract : By employing two easily-obtained organic linkers with bromine (Br) and iodine (I) groups, we firstly reveal the construction of water stable supramolecular porous structures with halogen dependent properties.